Pelatihan Pengelolaan Data Menggunakan Aplikasi Microsoft Excel Bagi Guru Di Sd 187 Kabupaten Barru - Fajrin Baids; Ibrahim, Nur Wahyuningsih; B, Nurul Mutahara; Said, Awayundu; Hisanan, Herawan (PT Ininnawa Paramacitra Edu, 2024)
Efficient management of academic and administrative data remains a challenge for many teachers in Indonesia, including those at UPTD SD 187 Barru. This training program was designed to enhance teachers' skills in utilizing Microsoft Excel, a crucial tool for data management in education. The one-day training covered topics such as Excel interface introduction, basic formulas like SUM and IF, and advanced features such as dropdown lists and complex IF formulas. Employing an interactive learning approach, the sessions combined theory and hands-on practice. Evaluation results showed significant improvements in participants' understanding and skills, as evidenced by their ability to independently create student assessment tables. The collaborative approach between lecturers and students played a key role in the training’s success. This program is expected to contribute to increased efficiency and accuracy in school data management while motivating teachers to further develop their technological competencies.